Tengunoibacter tsumagoiensis gen. nov., sp. nov., Dictyobacter kobayashii sp. nov., Dictyobacter alpinus sp. nov., and description of Dictyobacteraceae fam. nov. within the order Ktedonobacterales isolated from Tengu-no-mugimeshi, a soil-like granular mass of micro-organisms, and emended descriptions of the genera Ktedonobacter and Dictyobacter. Issue 7 (16th April 2019) - Wang, Chiung-mei; Zheng, Yu; Sakai, Yasuteru; Toyoda, Atsushi; Minakuchi, Yohei; Abe, Keietsu; Yokota, Akira; Yabe, Shuhei
Abstract : Three mesophilic, Gram-stain-positive, aerobic bacterial strains, designated Uno3 T, Uno11 T and Uno16 T, were isolated from a soil-like granular micro-organism mass (termed Tengu-no-mugimeshi) collected from Tsumagoi, Gunma, Japan. They grow at 11–37 °C and pH 4.0–8.0, form branched mycelia, and have a G+C content between 49.4–50.3 mol%. The major menaquinone and fatty acid of Uno3 T are MK-9 and iso-C16 : 0, respectively, whereas Uno11 T and Uno16 T share MK-9 (H2 ) and C16 : 1 -2OH. The major cell-wall sugars are mannose (Uno3 T and Uno11 T ) and glucose (Uno16 T ). Phylogenetic analysis based on 16S rRNA gene sequences indicated that these three strains belong to the order Ktedonobacterales and are most closely related to Dictyobacter aurantiacus S-27 T (sequence similarity of 91.3, 96.4 and 95.5 %). Average nucleotide identity values were <79.9 % among Uno11 T, Uno16 T and D. aurantiacus S-27 T, well below the 95–96 % species circumscription threshold. Based on phenotypic features and phylogenetic positions, we propose that Uno3 T represents a novel genus and species, Tengunoibacter tsumagoiensis gen. nov., sp. nov. (type strain Uno3 T =NBRC 113152 T =LMG 30471 T =BCRC 81113 T ) within the new family Dictyobacteraceae fam. nov. Strains Uno11 T and Uno16 T are also considered to represent novel species: Dictyobacter kobayashii sp. nov. (type strain Uno11 T =NBRC 113153 T =LMG 30472 T =BCRC 81114 T ) and Dictyobacter alpinus sp. nov. (type strain Uno16 T =NBRC 113154 T =BCRC 81115 T ). We also propose an emended description of the genus Dictyobacter, classifying it within family Dictyobacteraceae, and provide emended descriptions of the genera Dictyobacter and Ktedonobacter .